Protein kinase Pi65 regulates rice blast resistance through phosphorylation-dependent signaling and metabolic reprogramming - Wang, Lili; Chen, Hongwei; Zhou, Xiaohang; Yan, Bowen; Tang, Zhiqiang; Ma, Zuobin; Ma, Dianrong; Zheng, Wenjing (Frontiers in Genetics, 2026)
Rice blast is a major fungal disease that threatens global rice production and is caused by the fungus Magnaporthe oryzae. Therefore, cloning rice blast resistance-related genes, conducting indepth analyses of the interaction mechanisms between M. oryzae and rice, elucidating rice disease resistance pathways, and developing new resistant germplasms are crucial for ensuring food security. This study took the rice blast resistance-related protein kinase Pi65 as the research object and explored its regulatory role in the immune response of rice through protein phosphorylation omics and protein interaction verification. The experimental results demonstrated that Pi65 exhibited autophosphorylation kinase activity. Based on phosphoproteomic analysis, 572 and 107 differentially regulated phosphoproteins (DPPs) were identified in Pi65-knockout (KO) and Pi65-overexpression (OE) lines, respectively, compared with the wild type (WT). These DPPs showed significant changes in signal transduction, metabolic processes, and subcellular localization, indicating that altered Pi65 expression affects phosphorylation homeostasis in rice leaves. KEGG and GO enrichment analyses revealed that the DPPs in KO lines were mainly associated with biological processes such as nitrogen cycling and non-homologous end joining, whereas DPPs in OE lines were significantly enriched in pathways related to the calvin cycle, glycolysis, and RNA binding. Thus, Pi65 may participate in the regulation of cellular metabolism by modulating nuclear phosphorylation networks and post-transcriptional modification processes. Protein interaction validation experiments further confirmed that Pi65 directly interacted with the redox regulatory protein OsAPX4 and the phosphate transporter OsPHF1, linking Pi65 function to redox homeostasis and phosphorus signaling. These findings suggest that Pi65 acts as a key regulatory hub that integrates biotic and abiotic stress signals to modulate rice blast resistance via phosphorylation-dependent signaling cascades. This study provides new insights into the roles of plant kinases in multi-stress responses and offers potential candidate targets for genetic improvement of crop stress resistance.